(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Uzbekistan’s step on the path of independent development, in the re-perception of the history of the long struggle of our ancestors for freedom and liberty, national liberation movements and the process of formation of the modern national revival ideology as factors that ensured the achievement of state independence are of great social interest to historians today. is shooting One of the important events that left an indelible mark in the history of the Uzbek people was reflected in the autonomy of Turkestan, which embodied the ideas of freedom and independence, all the wishes of the people. Today, it is very important to study the history of the struggle for freedom of enlightened intellectuals of the people, especially the Jadids. In this article, we would like to express our thoughts about Mahmudhoja Behbudi’s efforts and results for the development of the future of the nation in the path of enlightenment.